2010
DOI: 10.1002/pon.1852
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient–provider communication for black women making decisions about breast cancer treatment

Abstract: Poor communication may impact treatment decision-making and, ultimately, outcomes. Important next steps will include quantifying Black women's patient-provider interactions and examining how these factors influence adherence behaviors. Ensuring that patients understand their diagnosis and treatment options will also be important for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 51 publications
6
45
0
2
Order By: Relevance
“…20 The lack of association for grade and treatment was also not surprising; providers may not emphasize grade during treatment discussions as much as they may highlight subtype and stage. Although our observations are provocative and consistent with other work describing associations for understanding general treatment rationales and benefits of therapy with receipt of care, 5,6,8,28,29 broader interpretation of our results is limited by a lack of detailed information on treatment discussions, information on trastuzumab, patient preferences, and if/how information was conveyed to patients. In addition to the potential importance of individualized tumor information, others have suggested that the ways recurrence and survival risks are presented may also impact receipt of chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…20 The lack of association for grade and treatment was also not surprising; providers may not emphasize grade during treatment discussions as much as they may highlight subtype and stage. Although our observations are provocative and consistent with other work describing associations for understanding general treatment rationales and benefits of therapy with receipt of care, 5,6,8,28,29 broader interpretation of our results is limited by a lack of detailed information on treatment discussions, information on trastuzumab, patient preferences, and if/how information was conveyed to patients. In addition to the potential importance of individualized tumor information, others have suggested that the ways recurrence and survival risks are presented may also impact receipt of chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…Other selected measures were based on the adherence model of health behavior 25,26 and included sociodemographic, psychosocial, attitudinal, patient-provider interaction, health care setting, and clinical (surgery, American Joint Committee on Cancer [version 6] stage, and chemotherapy use) factors relevant to adherence to medication regimens. ( t n e m r i a p m i e v i t i n g o C ) 7 1 = n ( e l b i g i l e n i e g a t S ) 30 Patient perceptions of patient-physician communication were assessed using the Makoul scale and Primary Care Assessment Survey (PCAS).…”
Section: Methodsmentioning
confidence: 99%
“…[31] Oysa sağlık personeli ile hasta arasındaki iletişimin yetersiz olması tedavi ile ilgili karar verme sürecini ve tedavinin sonuçlarını olumsuz etkileyebilir. [4] Hemşirelerin kanser hastalarına yeterli zamanı ayırmasına, hastalar ile iletişimlerini arttırmalarına gereksinim duyulmaktadır.…”
Section: Hastaların Sağlık Personelinin İletişimine Yönelik Değerlendunclassified
“…[4] Bu nedenle kanser hastalarının bilgi gereksinimlerini anlayabilmek için iletişim ve hastaların karar vermede desteklenmesi önemlidir. [5] Hastalar sağlık profesyonellerinden olumlu iletişim yanında bakım, destek [6] ve olayların anlayabilecekleri dilde anlatılmasını beklemektedirler.…”
Section: Introductionunclassified